Bovine Viral Diarrhea Virus Antigen and Immunoglobulin-G Detection in Unvaccinated Cattle - Suryohastari, Raden Rara Bhintarti; Saepulloh, Muharam; Jannah, Ana Roudlotul (Jurnal Sain Veteriner, 2025)
To address the community's nutritional for meat can be supported by importing cattle while maintaining vigilance against Bovine Viral Diarrhea (BVD), an infectious disease caused by the Bovine Viral Diarrhea Virus (BVDV). This pathogen is associated with gastrointestinal, respiratory, and reproductive issues in cattle worldwide. Consequently, controlling BVDV stands as a paramount measure in preventing BVD. One effective strategy in this endeavor is vaccination. The successful implementation of vaccination relies on acquiring comprehensive information about BVDV antigens and antibodies present in the serum of unvaccinated cattle, which can provide insights into the protein profile resulting from natural infection. This study aimed to detect BVDV antigen and immunoglobulin-G (IgG) based on molecular weight in protein profiles from various cattle breeds imported into Indonesia. Utilizing the SDS-PAGE method, the analysis results revealed protein bands at 55.3 kDa and 151.3 kDa were detected in the serum of BVD-positive cows, meanwhile, these specific profiles were absent in BVD-negative cows. It can be concluded that the 55.3 kDa represents a BVDV antigen, while the 151.3 kDa corresponds to an IgG antibody profile. These findings can serve as one of the basic foundations for developing a BVD vaccine for cattle populations.